Corporate Social Responsibility of Multinational Corporations in Foreign Countries: The case of the German Volkswagen Group in China - Opfer, Sarah Katharina (2017)
As the name indicates, Corporate Social Responsibility (CSR) is a business concept that ascribes social responsibilities to companies. This idea has a long history of several centuries, however it only attracted broad public attention recently. A universal definition of CSR, which would clearly specify the social responsibilities that corporations should comply with, does not exist to date. Which behaviour can be regarded as socially responsible? Generally, corporate social activities are to a great extent temporally and culturally determined, because they have to respond to the social sphere of the country they operate in. Especially Multinational Corporations face major challenges in implementing corporate social activities in foreign countries, since their inherent social understanding can be different. Nonetheless, CSR has a huge potential to improve living conditions of communities in developing countries, if CSR is responsive to local needs. It further has the potential to improve the competitive positioning of the corporation itself, if the social activities are incorporated into the business strategy. In short, CSR can create shared value, namely for the society and the corporation.